Is Drp1 a link between mitochondrial dysfunction and inflammation in Alzheimer’s disease? - Sbai, Oualid; Bazzani, Veronica; Tapaswi, Shreya; McHale, Joshua; Vascotto, Carlo; Perrone, Lorena (Frontiers in Molecular Neuroscience, 2023)
Recent advances highlight that Inflammation is critical to Alzheimer Disease (AD) pathogenesis. Indeed, several diseases characterized by inflammation are considered risk factors for AD, such as type 2 diabetes, obesity, hypertension, traumatic brain injury. Moreover, allelic variations in genes involved in the inflammatory cascade are risk factors for AD. AD is also characterized by mitochondrial dysfunction, which affects the energy homeostasis of the brain. The role of mitochondrial dysfunction has been characterized mostly in neuronal cells. However, recent data are demonstrating that mitochondrial dysfunction occurs also in inflammatory cells, promoting inflammation and the secretion of pro-inflammatory cytokines, which in turn induce neurodegeneration. In this review, we summarize the recent finding supporting the hypothesis of the inflammatory-amyloid cascade in AD. Moreover, we describe the recent data that demonstrate the link between altered mitochondrial dysfunction and the inflammatory cascade. We focus in summarizing the role of Drp1, which is involved in mitochondrial fission, showing that altered Drp1 activation affects the mitochondrial homeostasis and leads to the activation of the NLRP3 inflammasome, promoting the inflammatory cascade, which in turn aggravates Amyloid beta (Ab) deposition and tau-induced neurodegeneration, showing the relevance of this pro-inflammatory pathway as an early event in AD.